2018
DOI: 10.1093/eurpub/cky100
|View full text |Cite
|
Sign up to set email alerts
|

The association between discrimination and health: findings on Russian, Somali and Kurdish origin populations in Finland

Abstract: To promote the health of diverse populations, actions against racism and discrimination are highly needed, including initiatives that promote shared belonging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 34 publications
3
36
0
5
Order By: Relevance
“…Furthermore, we have indicated that comorbid affective symptoms are more common among substance using Kurds in particular . This study will expand previous knowledge on pre‐migration traumatic experiences, post‐migration perceived discrimination and substance use .…”
Section: Introductionsupporting
confidence: 58%
See 4 more Smart Citations
“…Furthermore, we have indicated that comorbid affective symptoms are more common among substance using Kurds in particular . This study will expand previous knowledge on pre‐migration traumatic experiences, post‐migration perceived discrimination and substance use .…”
Section: Introductionsupporting
confidence: 58%
“…We found no previous comparable research concerning forced migrants in their new host countries. It is possible that previous results among general populations or internally displaced people may not be comparable to international migrants facing specific challenges in new host countries . Our study makes a relevant contribution to the existing literature demonstrating an association between a hazardous pattern of alcohol use and traumatic experiences among Kurds, a forced migrant population.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations